Exploring the factors influencing consumers' choice of retail store when purchasing fresh meat in Malaysia - Chamhuri, N.; Batt, Peter (International Food and Agribusiness Management Association, 2013)
This research explores the preferred place for Malaysian consumers to purchase fresh meat. From four focus group discussions, participants indicated that their decision to purchase fresh meat from either a modern retail outlet or the traditional market was influenced by five key variables: perceptions of freshness, Halal assurance, a good relationship with retailers, a competitive price and a pleasant environment for shoppers. Results were subsequently validated in a quantitative survey of 250 respondents in the Klang Valley. Despite the increasing number of supermarkets and hypermarkets, not only are the traditional markets able to coexist with modern retail formats, but they remain the preferred place for respondents to purchase fresh meat.